1994
DOI: 10.1016/0387-7604(94)90091-4
|View full text |Cite
|
Sign up to set email alerts
|

Malonic aciduria

Abstract: Three infants with malonic aciduria are reported, one of whom could be studied in detail. All children had severe and progressive encephalopathy with intermittent ketoacidosis and hypoglycemia. One infant died of cardiomyopathy. Biochemical studies revealed that one patient had neither malonyl-CoA decarboxylase nor glutaryl-CoA dehydrogenase deficiencies. This variant of malonic aciduria is different from that of four patients previously reported, both in its clinical and biochemical presentations. The biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…It is speculated that MCD deficiency causes an excess of intramitochondrial malonyl-CoA, leading to the inhibition of methylmalonyl-CoA mutase and, subsequently, an increase in MMA. Two patients have been described with similar combined elevations of MA greater than MMA, but with normal MCD enzyme activity in fibroblast cultures12 13 suggesting that this disorder is heterogeneous. All of these patients have shown a variety of clinical features that include metabolic acidosis, developmental delay, seizures, cardiomyopathy, gastrointestinal distress and dysmorphic features, although normal development was also reported 11.…”
mentioning
confidence: 99%
“…It is speculated that MCD deficiency causes an excess of intramitochondrial malonyl-CoA, leading to the inhibition of methylmalonyl-CoA mutase and, subsequently, an increase in MMA. Two patients have been described with similar combined elevations of MA greater than MMA, but with normal MCD enzyme activity in fibroblast cultures12 13 suggesting that this disorder is heterogeneous. All of these patients have shown a variety of clinical features that include metabolic acidosis, developmental delay, seizures, cardiomyopathy, gastrointestinal distress and dysmorphic features, although normal development was also reported 11.…”
mentioning
confidence: 99%
“…Generalized cerebral and cerebellar atrophy is one of the prominent imaging findings . High intensities in the basal ganglions were reported in some patients . To the best of our knowledge, dentate nucleus hyperintensity has not been reported previously in MLYCD.…”
Section: Discussionmentioning
confidence: 74%
“…Both white and gray matter involvement was demonstrated together or alone in malonic aciduria [6][7][8]. Subcortical white matter intensity alterations, delayed myelination, cortical pachygyria, polymicrogyria, and periventricular heterotopia were reported in several cases [19,20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The main observations were generalized atrophy and white matter altered signals [de Wit et al, ; Celato et al, ]. In some cases, bilateral basal ganglia lesions [Ozand et al, ], pachygyria [de Wit et al, ], nodular heterotopias [de Wit et al, ], and polymicrogyria [Celato et al, ] were observed. In our case, no structural changes were detected by brain MRI, which was consistent with the patient's mild mental retardation.…”
Section: Discussionmentioning
confidence: 99%